Salivary Cytokines as Potential Diagnostic Biomarkers for Systemic Lupus Erythematosus Disease - Zeineb Zian; Assia Bouhoudan; Nadira Mourabit; Gholamreza Azizi; Mohcine Bennani Mechita (Hindawi Limited, 2021)
Systemic lupus erythematosus (SLE) is a complex autoimmune inflammatory disease characterized by an unknown etiology and a highly variable clinical presentation. This clinical heterogeneity might be explained by dysregulation of tolerance to self and apoptotic mechanisms, overproduction of autoantibodies, and abnormal cytokine levels. Cytokine imbalance levels have been associated with disease activity and severity in SLE patients. In the last years, salivary cytokines related to SLE have gained significant attention and researchers have begun to focus on the identification of cytokines in the saliva of SLE patients using it as a diagnostic fluid for the inflammatory process underlying SLE. This review highlights and summarizes recent studies revealing the cytokines that have been identified in the saliva of individuals with SLE. Data reported and discussed in this report may provide useful additional information to better understand the mechanisms associated with the disease.